pH Dependence of T2 for Hyperpolarizable 13C-Labelled Small Molecules Enables Spatially Resolved pH Measurement by Magnetic Resonance Imaging - Martin Grashei (Pharmaceuticals, 2021)
Hyperpolarized 13C magnetic resonance imaging often uses spin-echo-based pulse sequences that are sensitive to the transverse relaxation time T2. In this context, local T2-changes might introduce a quantification bias to imaging biomarkers. Here, we investigated the pH dependence of the apparent transverse relaxation time constant (denoted here as T2) of six 13C-labelled molecules. We obtained minimum and maximum T2 values within pH 1–13 at 14.1 T: [1‑13C]acetate (T2,min = 2.1 s; T2,max = 27.7 s), [1-13C]alanine (T2,min = 0.6 s; T2,max = 10.6 s), [1,4‑13C2]fumarate (T2,min = 3.0 s; T2,max = 18.9 s), [1-13C]lactate (T2,min = 0.7 s; T2,max = 12.6 s), [1‑13C]pyruvate (T2,min = 0.1 s; T2,max = 18.7 s) and 13C-urea (T2,min = 0.1 s; T2,max = 0.1 s). At 7 T, T2‑variation in the physiological pH range (pH 6.8–7.8) was highest for [1‑13C]pyruvate (ΔT2 = 0.95 s/0.1pH) and [1‑13C]acetate (ΔT2 = 0.44 s/0.1pH). Concentration, salt concentration, and temperature alterations caused T2 variations of up to 45.4% for [1-13C]acetate and 23.6% for [1-13C]pyruvate. For [1-13C]acetate, spatially resolved pH measurements using T2-mapping were demonstrated with 1.6 pH units accuracy in vitro. A strong proton exchange-based pH dependence of T2 suggests that pH alterations potentially influence signal strength for hyperpolarized 13C-acquisitions.